Principles of Buddhist Iconography And Iconometry With Special Reference To The Buddha Image - Wikramagamage, Chandra (My University, 2016)
Attached

In This study, the principles of Buddhist iconography and iconometry are discussed with special reference to the Buddha image, historically, theoretically and methodically. The major part of the thesis is devoted to giving a systematical account of Buddha iconometry together with some comparison with Egyptian, Greek and Roma iconometry, since no other student has yet attempted this. The first chapter gives a brief account of the history of Buddhist iconography and iconometry as well as of the techniques used in comparison with those of the Hindus and Jaina. In particular, the origin of the Buddha image is discussed. In the second chapter Buddhist gods, particularly the anthropomorphic representations of Great Wisdom (sammasambodhi) are described with reference to their theory and symbolism. In addition, the role the Buddha image played as a mean of meditation is also discussed as well as the Adibuddha, Buddha families and different manifestations. The subject matter of the third chapter sis the characteristic signs are discussed separately as they are laid down in Southern and Northern Buddhist scriptures. In the fourth chapter an attempt is made to clarify the theories and methods of proportions of standard human types common to Eastern and Western art. The fifth chapter gives the systematical order of Buddhist iconometry in terms of systems, types and methods.